Modelagem numérica de vigas compostas por perfis tubulares de aço preenchidos por concreto com protensão - Cristiane Caroline Campos Lopes (2020)
This research presents a numerical methodology capable of representing the behavior of composite beams, with passive external prestress, during fabrication and when subjected to loads. These composite beams consist of rectangular steel tubes filled with self-consolidating concrete. The passive external prestress method was developed at the beginning of the 1950 decade by Abraham Lipski and Louis Baes on I-shaped steel beams and it was patented as “Preflex”. The prestress forces are applied numerically in this work basically following two steps: Firstly, the rectangular steel tube is subjected to two concentrated vertical loads applied at the quarters of the span leading to tension stresses at the bottom flange of this section, that remain in the elastic domain. Secondly, the steel tube is filled with concrete and, when the concrete gets resistance, the vertical loads are removed. When the steel beam tries to come back to its initial position, the steel profile introduces compression stresses in the concrete core by the internal tensioned surface of the steel tube in contact with the concrete, defined as passive external prestress. The numerical models were developed in the finite element software ABAQUS and the results were validated through results found in the literature. Once the numerical modeling was validated, comparative analyses were performed and, finally, it was possible to observe the efficiency of passive prestressing in beams stiffness increasing, subject to service loads. As expected, the resistant capacity of the composite beams was not affected by the prestressing.